2021
DOI: 10.3389/fphar.2021.627738
|View full text |Cite
|
Sign up to set email alerts
|

Anacardium Occidentale L. Leaf Extracts Protect Against Glutamate/H2O2-Induced Oxidative Toxicity and Induce Neurite Outgrowth: The Involvement of SIRT1/Nrf2 Signaling Pathway and Teneurin 4 Transmembrane Protein

Abstract: Neurodegenerative diseases are linked to neuronal cell death and neurite outgrowth impairment that are often caused by oxidative stress. Natural products, which have neuroprotective against oxidative stress and neurite outgrowth inducing activity, could be potential candidates for alternative treatment of neurodegenerative diseases. This study aims to investigate the neuroprotective effects and neuritogenesis properties of Anacardium occidentale leaf extracts in cultured neuronal (HT22 and Neuro-2a) cells. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
5
25
0
Order By: Relevance
“…In Neuro2a cells, Ten-4 triggered neurite outgrowth by activation of focal adhesion kinase (FAK) and Rho-family small GTPases, Cdc42 and Rac1, key molecules for the membranous protrusion formation downstream of FAK [ 39 ]. Recently, herbal extracts such as Mucuna pruriens , Anacardium occidentale L., Glochidion zeylanicum , Vitis vinifera , and Camellia sinensis (oolong tea) were also reported to increase neurite outgrowth dependent on Ten-4 expression [ 31 , 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Neuro2a cells, Ten-4 triggered neurite outgrowth by activation of focal adhesion kinase (FAK) and Rho-family small GTPases, Cdc42 and Rac1, key molecules for the membranous protrusion formation downstream of FAK [ 39 ]. Recently, herbal extracts such as Mucuna pruriens , Anacardium occidentale L., Glochidion zeylanicum , Vitis vinifera , and Camellia sinensis (oolong tea) were also reported to increase neurite outgrowth dependent on Ten-4 expression [ 31 , 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, medicinal plant-derived natural compounds have received extensive attention as major sources of new therapeutic agents for treating neurodegenerative diseases and neurological disorders. Many of them have been shown to exert their neurotrophic effects by promoting neurite outgrowth [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Khan MM et al found that the activation of Nrf2 signaling could suppress oxidative stress by increasing the mRNA expression of antioxidant enzymes, including GPx-1, CAT, and SOD1 [34,35]. Moreover, upregulation of Nrf2 expression was associated with oxidative stress inhibition and protection against neuronal death [36,37]. Many studies have demonstrated that natural products could attenuate neurotoxicity against glutamate via the Nrf2 pathway [19,32,36].…”
Section: Discussionmentioning
confidence: 99%
“…The imbalances between free radicals and antioxidants (oxidative stress) have been implicated in the progression of neurodegenerative diseases [ 1 , 3 ]. During the last decade, polyphenolic compounds have been explored extensively in neuroprotective effects because of their antioxidant properties [ 13 , 32 , 33 , 34 , 35 ]. Moreover, indirect antioxidant compounds [ 36 ] (moderate antioxidant systems and related pathways, but not direct interactions with reactive species) such as docosahexaenoic acid (DHA) [ 37 ], Vitamin K [ 38 ], and sinapic acid [ 39 ] have emerged in alternative treatment of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these phenomena were further confirmed by the increased expression of neurite outgrowth markers GAP-43 and Ten-4. Several studies have reported that polyphenols, including gallic acid [ 32 , 34 ], catechin [ 13 , 40 , 41 ] and quercetin [ 33 , 42 , 43 ], promote neurite outgrowth activity. The presence of phenolic compounds as well as gallic acid, catechin, and quercetin in GZM extract may be responsible for the observed behavior ( Supplementary Figure S1 ) [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%